2018
DOI: 10.4178/epih.e2018048
|View full text |Cite
|
Sign up to set email alerts
|

The survival rate of patients with beta-thalassemia major and intermedia and its trends in recent years in Iran

Abstract: OBJECTIVESThalassemia is a common genetic disease in Iran, especially in the north and south of Iran. The present study sought to determine the survival rate of patients with thalassemia in highly endemic regions of Iran and its variation in patients born before and after 1971.METHODSThe present historical cohort study extracted data from the health records of patients with beta-thalassemia major, beta-thalassemia intermedia, and sickle beta-thalassemia who had presented to thalassemia treatment centers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
3
20
1
1
Order By: Relevance
“…The included studies were published from 1994 to 2018. Base on geographical location, five studies conducted in Iran 9,[20][21][22][23] , one in Italy, 24 and one in Cyprus. 25 Characteristics of the included studies presented in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published from 1994 to 2018. Base on geographical location, five studies conducted in Iran 9,[20][21][22][23] , one in Italy, 24 and one in Cyprus. 25 Characteristics of the included studies presented in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…9 Some factors affect on this increasing picture of TM survival including improving of surveillance in some parts of the world, improved treatment of cardiac complications, better accessibility to blood donor, blood screening for pathogens, treatment of infections, and treatment with deferoxamine. 10,11 In the Modell et al study, decreasing of cardiac disease in TM was reported as the main factor in increasing of survival. 12 Lower survival rate in some reigns in the world associated with availability of deferoxamine treatment and also related to burdensome iron chelation regimen refusal by TM patients.…”
Section: Introductionmentioning
confidence: 97%
“…Signifi cant success has been achieved with allogeneic bone marrow transplantation in patients with homozygous -thalassemia who have had an HLA-identical donor. The mortality from the procedure in these patients is quite high (30%), due to the complications of iron overload, but it is signifi cantly lower (below 10%) if the intervention is performed in early childhood [8]. The orofacial manifestations in people with thalassemia are numerous and intense.…”
Section: Disscusionmentioning
confidence: 99%
“…Prior report showed 381 patients required regular transfusion in Hong Kong 2 . Survival in patients with transfusion dependent thalassemia (TDT) improved with optimized care and newer iron chelating agents, long‐term complications surfaced as a result 3 . Bone health has become a major issue in the past decades as this specific cohort is aging 4 .…”
Section: Introductionmentioning
confidence: 99%